2008
DOI: 10.1057/ejis.2008.13
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of IT boundary objects, information infrastructures, and organisational identities: the introduction of 3D modelling technologies into the architecture, engineering, and construction industry

Abstract: In recent years, more companies engage in collaborative cross-organisational practices to achieve their business objectives. To cooperate effectively across boundaries requires organisations to overcome the tension between their distinct backgrounds and the need to create shared understandings with their partners for collaboration. This requires the creation of shared artefacts such as boundary objects. Whereas the past work on boundary objects has highlighted their role as translation devices, we examine them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(90 citation statements)
references
References 35 publications
1
86
0
3
Order By: Relevance
“…When the adoption of ICT has been studied, a wide range of theoretical frameworks has been applied to explain adoption and use of ICT. Some of these frameworks include the technology acceptance model, institutional theory, and social identity (see e.g., Gal et al 2008).…”
Section: Understanding Adoption and Use Of Bimmentioning
confidence: 99%
“…When the adoption of ICT has been studied, a wide range of theoretical frameworks has been applied to explain adoption and use of ICT. Some of these frameworks include the technology acceptance model, institutional theory, and social identity (see e.g., Gal et al 2008).…”
Section: Understanding Adoption and Use Of Bimmentioning
confidence: 99%
“…An important insight from boundary object research it that there is no need for the social worlds associated with a football club to reach consensus prior to engagement or collaboration (Boland & Tenkasi, 1995;Star & Griesemer, 1989): a perception of future achievable mutual outcomes may be sufficient. Gal et al (2008) highlight how change in boundary objects in turn enable change in both the infrastructures and the social identities of groups. As such, the boundary object forms and reforms relationships with the social identities of groups with which it shares common boundaries and with elements of the social infrastructure within which it is embedded.…”
Section: Inmentioning
confidence: 99%
“…Social infrastructure is a term used to define that which is required to make something else run or operate (Star & Ruhleder, 1996) and often consists of a series of taken for granted standardized practices, modes of communication, artefacts and interfaces. However, what is taken for granted in one social world may mean something different in other social worlds, creating the potential for conflict when these social worlds overlap in interface areas (Gal et al, 2008).…”
Section: Inmentioning
confidence: 99%
“…The findings from the case study showed that user-identity can both inhibit and enable assimilation. Gal et al (2008) studied the implementation of three-dimensional technologies into the architecture industry. They proposed a model to outline the relationship among information systems, information infrastructures and organisational identities and suggested that the systems help to form organisational identities and enable cross-organisational change.…”
Section: The Concept Of Identity In Organisationsmentioning
confidence: 99%
“…For instance, Lamb & Davidson (2005) described the transformations in the professional identities of groups of scientists associated with the introduction of a new information system. Similarly, Gal et al (2008) studied the transformations in the identity of an organisation in the American architecture industry as it adopted new systems while Walsham (1998) and Barrett & Walsham (1999) explored the links between the introduction of new information and communications technologies and changes in the identities of groups of professionals in the London Insurance Market. This kind of research can enrich our understanding of how individuals, groups and organisations incorporate technologyenabled changes in their environment into ongoing identity work; how new technologies get interpreted and feed into the way people perceive themselves and their organisations; how ongoing enactments of organisational interactions, practices and identities are influenced by the introduction of new technologies; and what role existing identities play in sense-making processes of new technologies.…”
Section: Future Directions For Research In Identity and Identificationmentioning
confidence: 99%